Bolstering the Preparation of School Counselor–Principal Teams for Work with LGBT Youth: Recommendations for Preparation Programs. Issue Volume 10:Issues 1(2016) (2nd January 2016) - Beck, Matthew J.
Abstract : This article outlines the role of counselor educators to assist school counselors-in-training in developing effective working relationships with school principals regarding lesbian, gay, bisexual, and transgender (LGBT) topics in K-12 settings. The author provides a rationale for implementing the school counselor–principal alliance in the preparation program, where future school counselors and principal trainees can work across programs and collaboratively address ways to strengthen each other's future roles as effective decision makers that promote success for LGBT students. Pedagogical recommendations for supporting and strengthening the school counselor-principal alliance within school counseling training programs are provided.